Volume Resistivity and Mechanical Behavior of Epoxy Nanocomposite Materials - Abdelkarim, M. F.; Nasrat, L. S.; Elkhodary, S. M.; Soliman, A. M.; Hassan, A. M.; Mansour, S. H. (Engineering, Technology & Applied Science Research, 2015)
Electrical and mechanical properties of polymer composite materials are investigated through the determination of resistivity and hardness for composites samples. Epoxy composite samples have been prepared with different concentrations of certain inorganic fillers such as; Titanium dioxide (TiO2) and Silica (SiO2), of various size (micro, nano and hybrid) to study the electrical and mechanical behavior. The volume resistivity reaches 3.23×1014 ohm.cm for the micro silica composite. Surface of composite material has been mechanically examined by hardness test. The results show that the resistivity of microcomposites and nanocmposites are increased with the decrease of filler concentration. But the resistivity of hybrid composites is increased with the increase of filler concentration. Maximum hardness value was obtained from hybrid silica composite with 0.1% filler concentration.